PERGESERAN NILAI ULOS PADA ADAT BATAK TOBA DI KELURAHAN SRI MERANTI KELURAHAN RUMBAI - Joel Frans; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The shift of Batak Toba Ulos Value in the Village of Sri Meranti Rumbai District is one of the research that has a purpose for the researchers themselves and other students. The key in this study are those who understand the customs of Batak, namely Batak Raja Adat consisting of any clans. The second objective is to know the values contained in ulos as well as the shifts occurring in the overseas lands. Analyze data in this research using Descriptive Qualitative Research Method. Qualitative Descriptive This is an analysis that seeks to provide a detailed description based on the facts obtained from the facts in the field and also supported by primary and secondary data to support the existing data. This qualitative research is presented with descriptions as well as aids with the calculation of the numbers, percentages and inserted in the table. The data will be analyzed descriptively. Therefore, the authors will develop concepts, collect data and facts that occur in the field. Based on the results of research in the field, the decline in ulos value has experienced the highest point, as it happens at this time is the number of Batak people in the Land of Perantauan do not know the meaning and value contained in Batak Ulos own. The research was conducted in Kelurahan Sri Meranti Rumbai District Pekanbaru City Riau Province. The results of this research show that there is a shift in the value of Ulos which is very signifikant in some elements, function, form, role in the implementation of traditional Batak event. Also giving sanctions for those who violate customary rules will be given sanctions that also experienced a shift from initial sanctions, this also affects the friction-friction with other cultures.Keywords: Value Ulos, Batak Toba, Tanah Parjalangan